A jó és rossz kölcsönhatása - Hecker-Réz, Róbert (Kultúratudományi Szemle, 2022)
The interaction between good and bad Robert Hecker-Réz The treatise examines the epistemological foundations of value judgment as the basis of inner orientation. First, the problem is formulated describing the internal dynamics of erroneous, incorrect and correct, excellent evaluations not on the basis of the confrontational, autocratic Anlantic model, but on the basis of Schleiermacher's oscillation of opposites, which overcomes this. This path is opened up through the complementary, interconnected discourses of several epochs in the history of philosophy. This is how Biehl and Luther, Ockham, the rich ideas of the English empiricists come to the fore, in order to immediately establish the autokheiros epistemological perspective and to sum it up in it.